An investigation of the loading and filtration properties of large-pore air filters for monodispersed aerosols - Leuschner, A. H.(Andries Hermann) (Stellenbosch : Stellenbosch University, 2012)
Dissertations (Ph. D.) -- Universiteit van Stellenbosch, 1983.